PERAN PEMERINTAH DESA DALAM PENANGGULANGAN PERNIKAHAN DINI DI DESA KURANJI KECAMATAM LABUAPI LOMBOK BARAT - Siti Hasanah; Firzhal Arzhi Jiwantara; Lukman (Bajang Institute, 2022)
The research objective was to determine the concept of a negative and positive active decision according to the law on government administration. This type of research is normative legal research, that normative legal research is research that includes research on legal principles, research on legal systematics, research on legal synchronization, legal history research, and comparative legal research. This research uses several approaches, namely legislation. -law (statute approach), Concept Approach (conceptual approach). The result of the research is that a Fiktip Decision is a decision that actually does not exist (non-being) but is considered to be there (being). Decisions that exist (being) at the level of positive law in Indonesia follow as stated in Article 1 number 9 of Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 concerning State Administrative Courts, Article 7 and Article 87 of Law Number 30 of 2014 Concerning Government Administration and Positive Functions in Law Number 30 of 2014 concerning Government Administration is not only related to Decisions, but also related to Actions, so there needs to be a change in labeling of Positive Fictional Decisions be a Positive Fictional Decision and / or Action so that it can represent the two elements contained in it